The “silver net of civilization”: Aesthetic Imperialism in Mary Shelley’s The Last Man - Schierenbeck, Daniel (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis essay examines the interrelations of religion, civilization, and imperialism in Shelley’s The Last Man. Though Shelley may envision the negative effects of imperialism in this novel, I argue that she does not critique the discourse of civilization itself, which helped justify imperialist designs. Furthermore, by viewing the aesthetic in Shelley’s novel as enmeshed with the political, I see Shelley’s aesthetic imperialism curiously aligned with the Evangelicals’ version of middle-class religion. Shelley would reject the Evangelicals’ arguments for the moral norms of Christianity as the means of civilization, but her aesthetic imperialism, through its emphasis on the self-regulation and discipline produced by literature and culture, also becomes a means to train the uncivilized in these bourgeois values.